The Cost of Foreign Exchange Intervention : Concepts and Measurement - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2016)
The accumulation of large foreign asset positions by many central banks through sustained foreign exchange (FX) intervention has raised questions about its associated fiscal costs. This paper clarifies conceptual issues regarding how to measure these costs both from an ex-post and an ex-ante (relevant for decision making) perspective, and estimates both marginal and total costs for 73 countries over the period 2002-13. We find ex-ante marginal costs for the median emerging market economy (EME) in the inter-quartile range of 2-5.5 percent per year; while ex-ante total costs (of sustaining FX positions) in the range of 0.2-0.7 percent of GDP per year for light interveners and 0.3-1.2 percent of GDP per year for heavy interveners. These estimates indicate that fiscal costs of sustained FX intervention (via expanding central bank balance sheets) are not negligible.